Limits of Possibility: Practices of Administrative Sanctions Against Russian Periodical Press at Beginning of 20th Century - I. V. Alferova; V. F. Blokhin (Научный диалог)
The study examines the mechanisms of censorship restrictions on Russian periodical press that had become widespread by the beginning of the 20th century. It explores the history of the development of censorship during the post-reform era and the stages of reorganization of the censorship apparatus in the context of changing Russian realities in the second half of the 19th century and the beginning of the 20th century. The issue of legislative initiatives regulating the coverage of domestic political events in the pages of Russian periodicals is addressed. Special attention is given to the practice of using administrative resources in the form of mandatory decrees by governors to establish control over local press. The documents for analysis were extracted by the authors from the archives of the Police Department of the State Archive of the Russian Federation. They contain information about specific instances of administrative penalties and fines imposed by governors on newspaper editors. Comparing this information with the content of articles subjected to penalties allowed for the identification of "the limits of possibility" for periodical press that existed locally in the perceptions of administrators. The review conducted led to the conclusion that mandatory decrees provided provincial administrations with the right, based on their own biases and convictions, to censor political content in print publications, thereby influencing public opinion.